2021
DOI: 10.3389/fpls.2020.607213
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals Candidate Genes Involved in Fruit Trait Variation in Persian Walnut (Juglans regia L.)

Abstract: Elucidating the genetic determinants of fruit quality traits in walnut is essential to breed new cultivars meeting the producers and consumers’ needs. We conducted a genome-wide association study (GWAS) using multi-locus models in a panel of 170 accessions of Juglans regia from the INRAE walnut germplasm collection, previously genotyped using the AxiomTMJ. regia 700K SNP array. We phenotyped the panel for 25 fruit traits related to morphometrics, shape, volume, weight, ease of cracking, and nutritional composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Taken together, the two genes are under positive selection are in J. mandshurica , but not in J. cathayensis . JMA026091 is a TVP38/TMEM64 family membrane protein encoding genes linked with the shell thickness of walnut in J. regia (Bernard et al ., 2021). The function of JMA025840 is unknown but, considering it is adjacent to JMA026091, we suspected that JMA025840 is actually under linked selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the two genes are under positive selection are in J. mandshurica , but not in J. cathayensis . JMA026091 is a TVP38/TMEM64 family membrane protein encoding genes linked with the shell thickness of walnut in J. regia (Bernard et al ., 2021). The function of JMA025840 is unknown but, considering it is adjacent to JMA026091, we suspected that JMA025840 is actually under linked selection.…”
Section: Resultsmentioning
confidence: 99%
“…4). One of the two genes under selection is a TVP38/TMEM64 family membrane protein encoding gene, which may link with the shell thickness of walnut (Bernard et al ., 2021). The pattern of selection is consistent with the result of IBE analysis in which genetic distance is not associated with environmental distance (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The nuts of both wild and cultivated Persian walnut are gathered and consumed [ 24 , 25 ], but wild trees produce smaller fruits (2–3 cm in diameter) with thicker shells, while domesticated varieties have larger fruits (3–6 cm in diameter) with thinner shells [ 26 ]. A genomic study of Iranian walnuts was able to link a SNP on chromosome 13 to shell thickness [ 27 ], and two other studies have reported candidate genes for shell thickness [ 28 , 29 ]. These inferences became possible with the release of the first walnut reference genome, Chandler v1.0 [ 30 ], which allowed whole-genome resequencing [ 29 , 31 , 32 ], the development of high-density genotyping tools [ 33 ], and the genetic dissection of agronomical traits in walnut, including the mentioned shell thickness [ 27 , 28 , 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…A genomic study of Iranian walnuts was able to link a SNP on chromosome 13 to shell thickness [ 27 ], and two other studies have reported candidate genes for shell thickness [ 28 , 29 ]. These inferences became possible with the release of the first walnut reference genome, Chandler v1.0 [ 30 ], which allowed whole-genome resequencing [ 29 , 31 , 32 ], the development of high-density genotyping tools [ 33 ], and the genetic dissection of agronomical traits in walnut, including the mentioned shell thickness [ 27 , 28 , 34 36 ]. Chromosome-level assemblies are now available for both J. regia and J. sigillata , the latter a close relative endemic in Guizhou, Sichuan, Southeast Xizang (Tibet), Yunnan, Bhutan, and Sikkim where its wood and nuts are used similarly to those of Persian walnut [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors from the BEL1-LIKE HOMEODO-MAIN (BLH) family were found to interact with OFPs in Arabidopsis, cotton, rice, and banana (Hackbusch et al, 2005;Li et al, 2011;Liu & Douglas, 2015;Pagnussat et al, 2007;Schmitz et al, 2015;Wang et al, 2016;Zhang et al, 2016). Moreover, Bernard et al (2021) found that a BLH protein was likely associated with walnut kernel weight. A homolog of BEL1-LIKE HOMEODOMAIN PROTEIN 2 (BLH2) underlying the QTL FWe-P2.4, detected with the strongest marker-FWe association, may thus affect fruit weight.…”
Section: Candidate Genes Were Identified For 53 Of the Highestconfide...mentioning
confidence: 99%